SEED AND FRUIT FOSSILS IN GREEK LIGNITE DEPOSITS - Αντωνιάδης, Π.; Μαυρίδου, Ε. (Bulletin of the Geological Society of Greece, 2018)
The aim of this study is to present a collection of seed and fruit fossils coming from several Greek lignite deposits. What is presented is part of an effort to create a complete collection that could be used in the future from scientists as a reference when studying Greek lignites and specially their paleoenvironment conditions. A general wetland model as a possible environment of peat formation is presented together with the representative flora for each wetland type. Seed and fruit fossils can not only provide adequate information for the reconstruction of paleoenvironment where lignite was formed, but can also contribute to the determination of age and stratigraphie classification of the lignite deposits. In three lignite deposits, namely Drama, Ag. Anargiri, and Lava, the information coming from found seed and fruit fossils was processed and the paleoenvironment conditions together with the age of the deposits were determined.